Insights on the Lewis Superacid Al(OTeF5)3: Solvent Adducts, Characterization and Properties. Issue 57 (18th August 2022) - Hoffmann, Kurt F.; Wiesner, Anja; Steinhauer, Simon; Riedel, Sebastian
Abstract: Preparation and characterization of the dimeric Lewis superacid [Al(OTeF5 )3 ]2 and various solvent adducts is presented. The latter range from thermally stable adducts to highly reactive, weakly bound species. DFT calculations on the ligand affinity of these Lewis acids were performed in order to rank their remaining Lewis acidity. An experimental proof of the Lewis acidity is provided by the reaction of solvent‐adducts of Al(OTeF5 )3 with [PPh4 ][SbF6 ] and OPEt3, respectively. Furthermore, their reactivity towards chloride and pentafluoroorthotellurate salts as well as (CH3 )3 SiCl and (CH3 )3 SiF is shown. This includes the formation of the dianion [Al(OTeF5 )5 ] 2− . Abstract : The dimeric Lewis superacid [Al(OTeF5 )3 ]2 and its solvent adducts are ready to test their strength in terms of fluoride ion affinity. While some of them are still highly reactive, others had too much coordinating solvent and remain stable but comparably unreactive. In here, their preparation, characterization and reactivity are reported in detail.